2017
DOI: 10.1002/2016jd025762
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical properties measurements by a CAPS single scattering albedo monitor: Comparisons between summer and winter in Beijing, China

Abstract: Aerosol optical properties were measured in Beijing in summer and winter using a state‐of‐the‐art cavity attenuated phase shift single scattering albedo monitor (CAPS PMssa) along with aerosol composition measurements by aerosol mass spectrometers and aethalometers. The SSA directly measured by the CAPS PMssa showed overall agreements with those derived from colocated measurements. However, substantial differences were observed during periods with low SSA values in both summer and winter, suggesting that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
4
33
1
Order By: Relevance
“…The SSA values were generally consistent with those observed in previous studies (Li et al, 2015c;Lee et al, 2007;Han et al, 2015a;Han et al, 2017), e.g., 0.85 -0.91 during the fall of 2014 (Han et al, 2015a) and 0.85 (±0.04) in the winter of 2015 (Han et al, 2017). We also observed slightly lower values at lower altitudes, indicating an enhanced BC absorption due to the influences of local emissions (Sun et al, 2015a;Sun et al, 2010).…”
Section: Vertical Co-variations Of Pollutantssupporting
confidence: 80%
“…The SSA values were generally consistent with those observed in previous studies (Li et al, 2015c;Lee et al, 2007;Han et al, 2015a;Han et al, 2017), e.g., 0.85 -0.91 during the fall of 2014 (Han et al, 2015a) and 0.85 (±0.04) in the winter of 2015 (Han et al, 2017). We also observed slightly lower values at lower altitudes, indicating an enhanced BC absorption due to the influences of local emissions (Sun et al, 2015a;Sun et al, 2010).…”
Section: Vertical Co-variations Of Pollutantssupporting
confidence: 80%
“…Studies in Los Angeles (Jacobson, 1998), Mexico City (Castro et al, 2001;Raga et al, 2001;Li et al, 2011), São Paulo (de Miranda et al, 2005), Houston (Flynn et al, 2010), Europe (Real and Sartelet, 2011), and Russia (Péré et al, 2015) have found that aerosols reduce ozone concentration by 5 %-30 % by attenuating photolysis frequencies. Studies in the eastern United States have shown that scattering aerosols increase ozone concentration by 5 %-60 % by increasing the photolysis frequencies (Dickerson et al, 1997;He and Carmichael, 1999). Therefore, it is necessary to quantitatively evaluate the effect of aerosols on photolysis frequencies for a better understanding of ozone formation under highly polluted conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The existing profile inversion approaches for MAX-DOAS can be sorted into two groups: inversion algorithms based on the optimal estimation (OE) method and iterative approaches, e.g. the Gauß-Newton or Levenberg-Marquardt methods (Rodgers, 2000;Frieß et al, 2006Frieß et al, , 2011Wittrock, 2006;Irie et al, 2008Irie et al, , 2011Clémer et al, 2010;Yilmaz, 2012;Hartl and Wenig, 2013;Y. Wang et al, 2013a, b), and the so-called parameterized approaches using look-up tables (X.…”
Section: Introductionmentioning
confidence: 99%